The Effects of Filter Cake and Bagasse Ash to Growth and NPK Uptake by Sugarcane (Saccharum Officinarum L.) at Ultisols in Tulang Bawang, Lampung, Indonesia - Heri Soegianto; Azwar Ma’as; Makruf Nurudin; Sri Nuryani Hidayah Utami (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2017)
The available soils for surgarcane plantation is Ultisols. However, the Ultisols has some limitations on its chemical fertility. Efforts to improve the quality of the soil can be done with applying organic matter such as filter cake and bagasse ash resulting from the process of making sugar from sugarcane. This study was proposed to determine the effects of bagasse ash and filter cake to availabilities of NPK in the soil and NPK uptakes by sugarcane, so that they were expected to be able to improve maximum sugarcane growth in Ultisols in Tulang Bawang. This field research used completely randomized design with two factors. The first factor was the bagasse ash doses in four levels: without bagasse ash (A0), 10 ton/ha of dry bagasse ash (A1), 20 ton/ha of dry bagasse ash (A2), and 40 ton/ha of dry bagasse ash (A3). The second factor was the filter cake doses in four levels: without filter cake (B0), 20 ton/ha of dry filter cake (B1), 40 ton/ha of dry filter cake (B2), and 80 ton/ha of dry filter cake (B3). There were a total of 16 combinations of treatment with 3 blocks as repetitions. Data were analyzed by using F-test with 5% significance. When analysis result showed significant differences between treatments, it was then followed by DMR test with 5% significance level for normal data. The results showed that the improvement of NPK status of Ultisols in Lampung might be achieved by applying the filter cake and bagasse ash techniques. Some results of this study showed that treatment of 40 ton/ha bagasse ash for NPK uptakes was significantly different and higher than without bagasse ash treatment. Treatment of 80 ton/ha filter cake for NPK uptakes was significantly different and higher than without filter cake treatment. The highest N uptake (27.84 kg/ha) was in sugarcane at 2 MAP with 80 ton/ha filter cake treatment. The highest P uptake (11.59 kg/ha) was in sugarcane at 2 MAP with 40 ton/ha bagasse ash treatment. The highest K uptake (117.67 kg/ha) was in sugarcane at 8 MAP with 80 ton/ha filter cake treatment. Treatment of 80 ton/ha filter cake influenced significantly to the sugarcane height compared to without filter cake and 20 ton/ha filter cake treatment, but it did not differ significantly compared to 40 ton/ha filter cake treatment. The highest sugarcane (167.99 cm) was at 80 ton/ha filter cake treatment. Filter cake dose treatments did not influence significantly the numbers of saplings and stem diameter of sugarcane aged 8 MAP.